Assessment of Corneal Alterations by Confocal Microscopy in Vernal Keratoconjunctivitis. (January 2015) - Nebbioso, Marcella; Zicari, Anna Maria; Lollobrigida, Valeria; Marenco, Marco; Duse, Marzia
Abstract Background: Vernal keratoconjunctivitis (VKC) is a bilateral chronic, seasonally exacerbated inflammation of the ocular surface that especially affects male children and young boys. Aim: To evaluate the corneal microscopic features of patients affected by VKC and to assess whether some corneal changes were associated with specific ocular symptoms and/or signs. Methods: 20 children aged between 4 and 14 years were enrolled. All patients underwent corneal confocal microscopy by Confoscan CS3 (Nidek). 350 images of the central cornea of each eye were obtained with a ×40 noncontact lens 3, 5 micron gap in automode. Results: Some alterations of the sub-basal and stromal corneal nerves were detected. These alterations were more evident in patients with higher severity of photophobia. On the other hand, there were scarce other signs of the anterior segment of the eye. Conclusions: Our preliminary findings show that there is another group of patients affected by VKC, characterized by an intense photophobia caused by corneal damage and without other significant ocular alterations. Therefore confocal microscopy may be useful for an early identification of corneal alterations before the onset of severe ocular symptoms and to set an appropriate therapeutic management.